Staging Parkinson's disease according to the MNCD classification correlates with caregiver burden - Diego Santos‐García; Teresa deDeus Fonticoba; Carlos Cores Bartolomé; María J. Feal Painceiras; Iago García Díaz; María Cristina Íñiguez Alvarado; Jose Manuel Paz; Silvia Jesús; Marina Cosgaya; Juan García Caldentey; Nuria Caballol; Ines Legarda; et al. (Brain and Behavior, 2023)
Abstract Background and objective Recently, we demonstrated that staging Parkinson's disease (PD) with a novel simple classification called MNCD, based on four axes (motor, non‐motor, cognition, and dependency) and five stages, correlated with disease severity and patients’ quality of life. Here, we analyzed the correlation of MNCD staging with PD caregiver's status. Patients and methods Data from the baseline visit of PD patients and their principal caregiver recruited from 35 centers in Spain from the COPPADIS cohort from January 2016 to November 2017 were used to apply the MNCD total score (from 0 to 12) and MNCD stages (from 1 to 5) in this cross‐sectional analysis. Caregivers completed the Zarit Caregiver Burden Inventory (ZCBI), Caregiver Strain Index (CSI), Beck Depression Inventory‐II (BDI‐II), PQ‐10, and EUROHIS‐QOL 8‐item index (EUROHIS‐QOL8). Results Two hundred and twenty‐four PD patients (63 ± 9.6 years old; 61.2% males) and their caregivers (58.5 ± 12.1 years old; 67.9% females) were included. The frequency of MNCD stages was 1, 7.6%; 2, 58.9%; 3, 31.3%; and 4–5, 2.2%. A more advanced MNCD stage was associated with a higher score on the ZCBI (p < .0001) and CSI (p < .0001), and a lower score on the PQ‐10 (p = .001), but no significant differences were observed in the BDI‐II (p = .310) and EUROHIS‐QOL8 (p = .133). Moderate correlations were observed between the MNCD total score and the ZCBI (r = .496; p < .0001), CSI (r = .433; p < .0001), and BDI‐II (r = .306; p < .0001) in caregivers. Conclusion Staging PD according to the MNCD classification is correlated with caregivers’ strain and burden.